Serum lactate levels are an independent marker for complications in acute pulmonary embolism: from the PERT registry. (25th November 2020) - Wasserstrum, Y; Lotan, D; Oren, D; Sanalla, S; Itelman, E; Dekel, S; Beigel, R; Shlomo, N; Matetzky, S
Abstract: Introduction: Serum lactate is a marker for the presence and severity of imbalances between tissue oxygen supply and demand. There are only scare data regarding the significance of arterial lactate in PE patients. Purpose: We sought to explore the significance of venous serum lactate as a short- and long-term predictor of adverse outcomes. Methods: We prospectively enrolled 570 patients with topographically-confirmed pulmonary embolism, hospitalized in our center during 2016–2019. Patient's data was collected using an electronic medical record and follow-up interviews via telephone. The combined end point of hemodynamic instability, shock, mechanical ventilation, or need for CPR was prospectively documented during hospitalization as well as 1-year mortality. Results: The analysis included 461 consecutive patients with available clinical data including venous lactate. The median age was 69 years, and 262 (58%) were female. Median serum lactate levels were 21 mg/dL (IQR 16–31). The composite endpoint was documented in 92 patients (20%), and lactate levels above 21 mg/dl had a higher incidence of the composite end point (26% vs, 14%, p=0.002). Similar findings were seen when adding either the need for escalating therapy (44% vs. 24%, p<0.001), in-hospital mortality (31% vs. 16%, p=0.001) or 30-day mortality (27% vs. 21%, p<0.001) to the previous composite. One-year mortality was significantly higher in the higher lactate group (17% vs 5%, p<0.001), and a lactate level above 21 mg/dL was independently associated with 1-year mortality in a Cox-regression model adjusted for age, gender and a history of heart failure or malignancy, HR 2.5 (95% CI 1.7–3.9). In subgroup analyses, lactate levels were associated with 1-year mortality regardless of age or gender. Similar predictive trends for 1-year mortality were seen in patients stratified by diabetes status, a current malignancy, PE risk and right-ventricle abnormalities (see figure). Conclusions: Venous serum lactate levels are associated with a myriad of in-hospital adverse outcomes, as well as long-term mortality. In a 1-year follow-up, a higher lactate level was predictive of mortality across various subgroups, with higher hazard ratios seen specifically in lower-risk patients. Further studies are needed in order to evaluate the possible prognostic role of the change in serum lactate during PE management. Funding Acknowledgement: Type of funding source: None